Abdominal cocoon syndrome: Rare cause of intestinal obstruction—Case report and systematic review of literature. Issue 27 (8th July 2022) - Chorti, Angeliki; Panidis, Stavros; Konstantinidis, Dimitrios; Cheva, Angeliki; Papavramidis, Theodossis; Michalopoulos, Antonios; Paramythiotis, Daniel
Abstract : Background: Abdominal cocoon or sclerosing encapsulating peritonitis is an uncommon condition in which the small bowel is completely or partially encased by a thick fibrotic membrane. Our study presents a case of sclerosing encapsulating peritonitis and conducts a literature review. Methods: A bibliographic research was conducted. Our research comprised 97 articles. Gender, age, symptoms, diagnostic procedures, and treatment were all included in the database of patient characteristics. Case presentation: A 51-year-old man complaining of a 2-day history of minor diffuse abdominal pain, loss of appetite, and constipation was presented in emergency department. Physical examination was indicative of intestinal obstruction. Laboratory tests were normal. Diffuse intraperitoneal fluid and dilated small intestinal loops were discovered on computed tomography (CT). An exploratory laparotomy was recommended, in which the sac membrane was removed and adhesiolysis was performed. He was discharged on the tenth postoperative day. Results: There were 240 cases of abdominal cocoon syndrome in total. In terms of gender, 151 of 240 (62.9%) were male and 89 of 240 (37%) were female. Ages between 20 and 40 are most affected. Symptoms include abdominal pain and obstruction signs. For the diagnosis of abdominal cocoon syndrome, CT may be the gold standard imaging method. The surgical operation was the treatment of choice in the vast majority of cases (96.7%). Only 69 of 239 patients (28.9%) were detected prior to surgery, and CT was applied in these cases. Conclusion: Abdominal cocoon is a rare condition marked by recurrent episodes of intestinal obstruction. Surgical therapy is the most effective treatment option.